Elasticities of Food Demand in Germany - A Demand System Analysis Using Disaggregated Household Scanner Data - Jonas Peltner; Silke Thiele (German Journal of Agricultural Economics (GJAE), 2021)
This paper presents price and income elasticities of food demand for Germany. Using disaggregated household scanner data and the Quadratic Almost Ideal Demand System (QUAIDS). The QUAIDS is modified to account for censoring and include household demographics. Furthermore, a two-stage budgeting approach is used to more accurately reflect households' purchasing behaviour. Having disaggregated data also allowed to include convenience aspects into the demand system. High expenditure elasticities are found for fruits and nuts and meat, fish and eggs. The highest own-price elasticity is found for beverages. At the second stage, the bread toppings group reveals new insights into demand relations between cold cuts, cheese and other spreads. Cold cuts have both the highest expenditure and own-price elasticity. Cross-price elasticities indicate mostly complementary relations between cold cuts and other bread toppings. Comparing different income groups shows that expenditure elasticities of raw foods or basic ingredient foods tend to decrease as income increases, whereas expenditure elasticities of foods that require minimal or no preparation tend to increase with income. In conclusion, this study stresses the need for regularly updated elasticities of food demand that reflect up-to-date consumption behavior.
Keywords: 330; food demand; elasticities; Germany; QUAIDS